Interaction of material stiffness and negative pressure to enhance differentiation of bone marrow‐derived stem cells and osteoblast proliferation. (9th January 2020) - Wang, Rui; Thayer, Patrick; Goldstein, Aaron; Wagner, William D.
Abstract: Negative pressure wound therapy (NPWT) results in improved wound repair and the combined use of NPWT with elastomeric materials may further stimulate and accelerate tissue repair. No firmly established treatment modalities using both NPWT and biomaterials exist for orthopedic application. The goal of this study was to investigate the response of osteoblasts and bone marrow‐derived mesenchymal stem cells to negative pressure and to determine whether a newly developed elastic osteomimetic bone repair material (BRM), a blend of type I collagen, chondroitin 6‐sulfate, and poly (octanediol citrate) could enhance the osteoblastic phenotype. The results indicate that proliferation and alkaline phosphatase activity of hFOB1.19 osteoblasts were significantly increased with exposure to 12 hr of negative pressure (−125 mmHg). Follow‐on studies with rat and human mesenchymal stem cells confirmed that negative pressure enhanced osteoblastic maturation. In addition, a significant interaction of negative pressure and electrospun BRM resulted in increased mRNA expression of alkaline phosphatase, osteopontin, collagen1α2, and HIF1α, whereas little or no effect on these genes was observed on electrospun collagen or tissue culture plastic. Together, these results suggest that the use of this novel biomaterial, BRM, with NPWT may ultimately translate into a safe and cost‐effective clinical application to accelerate bone repair.